Analisis Protokol Routing Aomdv Pada Vehicular Ad Hoc Network Di Pekanbaru (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The increasing number of vehicles per year causes problems not only pollution but also congestion and traffic accident which continue to increase every year. So we need a system that can help reducecongestion and accidents such as Intelligent Transportation System (ITS). With the increase in information technology, especially computer networks and the internet, researchers in this field try togive their contribution in realizing safety and comfort in driving. One popular research topic in the computer network and automotive industry is the vehicular ad-hoc network (VANET). The purpose ofthe VANET research is to develop a communication system on vehicles that enabling fast and efficient data exchange so that it can be used as a traffic information system. In this study, the testing of theAOMDV (Ad-hoc on Demand Multipath Distance Vector) routing protocol was used by using a scenario of changing the number of nodes and the speed of the nodes. The method used in this study isa simulation using SUMO and NS-2 and measured using the parameters of throughput, end to end delay and packet loss. From the simulation results, testing the change scenario the number of nodes inthe AOMDV protocol has an average throughput value of 319.9375 kbps, end-to-end delay 0.159667 s and packet loss 8.0831%.Keywords: VANET, AOMDV, NS-2, SUMO